Stakeholder Perspective of Value Creation in the Affordable Housing Market in South Arica - Dyantyis, Nwabisa (University of the Witwatersrand, Johannesburg, 2024)
Access to adequate housing is a global crisis and requires a concerted effort by both private and private sector actors in the housing market. South Africa has made great stride but faces challenges in the provision of affordable housing segment due to the multisectoral multidimension complexity of the delivery framework of affordable housing. This study reflects on the body of work by scholars to study the affordable housing delivery framework, which has looked at the mechanic of the affordable housing market and explored the challenges in the tools, frameworks, resource allocations and institutional arrangements, for the delivery of quality affordable housing at scale and in a sustainable manner. The stakeholder theory provides a framework for the exploration of the analysis of the multistakeholder delivery framework of affordable housing. Through the application of the literature, that relates to value creation, enables an exploration of the affordable housing market and the value that is created and allocated by and to stakeholders. For the purpose of the qualitative study interviewing twelve respondents from the three groups of supply side stakeholders in the affordable housing market, namely government, financiers, and developers; using semi-structured interviews, whose perspective was the primary data sources for this study. The interviews were recorded, transcribed and analysis to extract the themes that underpin the perspectives of stakeholders in the affordable housing market in South Africa. This study explores articulates the relationship between institutional stakeholders in the affordable housing supply chain segment to unlock the challenges constraining affordable housing delivery in South Africa. The outcomes of this basic research will contribute to further study of the affordable housing segment is contributing to the knowledge of mechanism of the market and stakeholder arrangements that create value in this housing segment and makes proposals for further study in this housing segment
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Affordable Housing; Value creation; Stakeholder; UCTD; SDG-8: Decent work and economic growth